Rhetorical Landscapes of Teaching Philosophy Statements: A Genre Analysis - Pandey, Hem Lal; Giri, Pradip Raj (SCHOLARS: Journal of Arts & Humanities, 2025)
This paper conceptualizes the teaching philosophy statement (TPS) as a genre, examining how composers articulate their envisioned perspectives, styles, views, and commitments of their teaching journey. By analyzing five TPSs written by prospective instructors from five departments of Humanities, the study investigates this genre’s defining features and roles in relation to the writers’ stated positionalities and strategies of pedagogical practices in the university classrooms. The primary texts are sourced from the University of Michigan’s repository. Employing Johnny Saldaña’s pattern coding methodology, the paper critically examines the TPS texts through the lens of genre criticism as advanced by theorists like Carolyn Miller and Charles Bazerman. The analysis explores how TPS constructs a rhetorical structure within the interplay of personal values and the institutional, disciplinary, and social contexts. This study underscores the significance of the genre for fostering writers’ rhetorical awareness in navigating transitions from graduate student identities to the roles of adjuncts, lecturers, or tenure-track professors. By illustrating the generic attributes of the selected TPSs, the paper highlights the genre as a tool for the writers to exhibit their professional teaching development and academic identity formation.